THE PERCEPTIONS OF THE NURSE CONCERNING THE COMPLETENESS OF THE ASSISTANCE - IIka Chediak Pinho; Josilucy Cristine Brito Aguiar Siqueira; Lícia Maria Oliveira Pinho (Universidade Federal de Goias, 2006)
ABSTRACT: This study had as aim to know the meaning of health integrality for nurses of a Primary Health Services in Goiânia, Goiás, by a descriptive study in a qualitative approach. From interviewed nurses speeches two categories has emerged: "Completeness: between knowing and applying" and "Completeness: the unprepared to deal with the subjectivity of the other one". The subject that emerged was nurse's perceptions concerning the completeness of the assistance. This subject show the story of the nurses who know, are unaware of and/or confuse about the completeness meaning, applying them or not to their daily activities. The involvement and respect with the patients, however, reveals the precarious interaction and unprepared to deal with the subjective dimension in the assistance practice. The completeness does not have to be made into a concept, but in health care practice that deals life, respect to the other and differences among human beings valuation. KEY WORDS: Nursing Care; Nursing Education; Comprehensive Health Care.